2021
DOI: 10.3390/vaccines9020167
|View full text |Cite
|
Sign up to set email alerts
|

Porvac® Subunit Vaccine E2-CD154 Induces Remarkable Rapid Protection against Classical Swine Fever Virus

Abstract: Live attenuated C-strain classical swine fever vaccines provide early onset protection. These vaccines confer effective protection against the disease at 5–7 days post-vaccination. It was previously reported that intramuscular administration of the Porvac® vaccine protects against highly virulent classical swine fever virus (CSFV) “Margarita” strain as early as seven days post-vaccination. In order to identify how rapidly protection against CSFV is conferred after a single dose of the Porvac® subunit vaccine E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Porvac® is a Cuban subunit marker vaccine against CSFV, which is based on a recombinant chimeric antigen comprising the E2 protein of CSFV and the molecular adjuvant CD154. This vaccine has been safe and capable of inducing an unusually rapid onset of protection against a challenge with a highly pathogenic CSFV strain, which is similar to the one described for MLV [9][10][11] . Porvac® induces both high neutralizing antibodies (NAb) titers and cell-mediated immune response and can interfere with the transmission of the virus from pregnant sows to their offspring 12 .…”
Section: Introductionmentioning
confidence: 76%
“…Porvac® is a Cuban subunit marker vaccine against CSFV, which is based on a recombinant chimeric antigen comprising the E2 protein of CSFV and the molecular adjuvant CD154. This vaccine has been safe and capable of inducing an unusually rapid onset of protection against a challenge with a highly pathogenic CSFV strain, which is similar to the one described for MLV [9][10][11] . Porvac® induces both high neutralizing antibodies (NAb) titers and cell-mediated immune response and can interfere with the transmission of the virus from pregnant sows to their offspring 12 .…”
Section: Introductionmentioning
confidence: 76%
“…Recent studies indicated the safety and efficacy of various CSF-E2 subunit protein-based non-infectious marker vaccines on breeding pigs under field or experimental conditions [ 19 20 21 22 ]. Likewise, in trial 1 of this study, high safety and immunity were obtained by the application of Bayovac CSF-E2 vaccine on pregnant sows in field farms.…”
Section: Discussionmentioning
confidence: 99%
“…The latter relies on antibody detection against the CSFV E rns protein to identify infection with field virus [ 4 ]. Moreover, recent studies exhibited their efficacy on early protection and vertical transmission prevention against CSF infection under experimental or field conditions [ 19 20 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of glycosylation sites has shown promise for the development of attenuated vaccine strains [181]. One further approach has been production of a fusion protein, combining the E2 protein to the extracellular segment of the host CD154 molecule, which is licensed as Povac ® in Cuba [222,223]. Another fusion protein vaccine combines the E2 protein with the host Fc region of IgG.…”
Section: Classical Swine Fevermentioning
confidence: 99%